2020
DOI: 10.3390/ani10071143
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance, Milk Composition and Milk Fatty Acids of Goats Supplemented with Sunflower and Linseed Whole Seeds in Grass Silage-Based Diets

Abstract: The objective of this study was to determine productive performance, milk composition and milk fatty acids (FA) of goats supplemented with sunflower and linseed whole seeds in grass silage-based diets. Nine Alpine goats were grouped in a replicated 3 × 3 Latin square design (n = 3), that included three 21-d periods. Treatments were based on grass silage offered ad libitum and a concentrate mixture supplemented with either 40 g/d of Megalac-R® (control), 80 g/d of sunflower seed (SF), or 80 g/d of linse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…This probably favored a more efficient use of the ammonia originated by the rumen degradable protein of the SF and SFS diets. Our results also coincide with a positive N balance reported in lactating does fed whole sunflower seeds or linseed [24].…”
Section: Nitrogen Balancesupporting
confidence: 91%
See 2 more Smart Citations
“…This probably favored a more efficient use of the ammonia originated by the rumen degradable protein of the SF and SFS diets. Our results also coincide with a positive N balance reported in lactating does fed whole sunflower seeds or linseed [24].…”
Section: Nitrogen Balancesupporting
confidence: 91%
“…Both SF and SFS had no effect on DM (1124 ± 85.7 g/d) and OM (1781 ± 182 g/d) intakes (Table 3), which partly agrees with what was previously reported both in lactating sheep [20,22,23] and goats [24,25], when animals were fed with either sunflower seeds or sunflower oil. Gomez-Cortés et al [23] obtained a rise in DM intake when sheep were supplemented with 2% DM sunflower oil in a diet, with a diet based on 50% forage and 50% concentrate; however, contrary to the present results, Ivan et al [21], reported a decrease in DMI with low-and high-forage diets with two protein levels of crushed sunflower seed supplementation.…”
Section: Nutrient Intake and Digestibilitysupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of effects on productive traits, such as milk yield, body conditions score, and body weight may be due to the relatively small amount of oil supplementation used in this study (4% DM). This agrees with previous studies where goats were fed with calcium soaps from palm, canola, and safflower oils ( 4 ) and when goats were supplemented with sunflower and linseed whole seeds ( 31 ). In those studies, oilseeds fed as calcium soaps or as whole seeds did not promote negative effects on overall animal productive traits and treatments were offered at <5% DM inclusion.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, some research efforts have been made to improve dietary energy supply in dairy goat diets. For example, in central Mexico, whole seeds from different oilseeds, such as sunflower and linseed, have been included in grass silage-based diets [ 36 ], while calcium soaps from canola and safflower oils [ 37 ] have also been included in goat diets without negative effect on overall nutrient intake and digestibility.…”
Section: Goat Production Systemsmentioning
confidence: 99%